THE RELATIONSHIP BETWEEN COMMUNITY BEHAVIOR AND TREATMENT OF SYMPTOMS OF INCREASED URIC ACID LEVELS IN KAYEE LEE VILLAGE, WANT JAYA DISTRICT, ACEH BESAR REGENCY - Maulida; Eridha Putra; Aina Please (International Conference on Education, Science, Technology and Health (ICONESTH), 2023)
The body's purine levels are too high, causing the body's uric acid levels to increase, crystals forming in the joints, causing joint discomfort. If there is too much uric acid in the blood, crystals form in the joint fluid. Gout develops into a disease. Gout is characterized by pain, stiffness and inflammation of the joints, problems with joint movement, and decreased muscle strength. This pain is worsened when doing activities that involve the joints and is reduced when resting. Joint pain is generally felt in the morning followed by inflammation, redness in the painful area, and weakness. The first treatment for gout joint pain in general is pharmacological. Pharmacological drugs are the most frequently used form of pain control. Pharmacological drugs consumed too often will affect the action of the drug in the body because the elderly have experienced various changes in body function. This research is descriptive analytical with a cross sectional approach, the population in this study is the people of Kaye Lee village who have been diagnosed with gout and are active in posyandu activities, totaling 32 people. Based on the results of research from 32 respondents, it was found that of the 23 respondents (100%) who had good knowledge, of which the majority had treatment, 18 (78.3%) respondents, of the 24 (100%) respondents who had a positive attitude, the majority had treatment. 18 (75.0%) respondents, of the 21 (100%) respondents who had the majority action, 16 (76.2%) respondents had treatment. The results of statistical tests obtained a p value of 0.001, it can be concluded that there is a relationship between community behavior and handling of symptoms of increased uric acid levels in Kayee Lee Village, Want Jaya District, Aceh Besar Regency.